2003
DOI: 10.1097/01.ogx.0000086420.13848.89
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Subgaleal Hemorrhage and Its Relationship to Delivery by Vacuum Extraction

Abstract: Subgaleal hemorrhage is a rare condition of the neonate often associated with instrumental delivery. It is a potentially fatal condition that is often underreported and underdiagnosed. The vacuum extractor is being advocated as the instrument of first choice for assisted vaginal delivery, but appears to be associated with an increased incidence of subgaleal hemorrhage. It is widely believed that the vacuum cup will dislodge before causing serious fetal trauma. Because of the ease of application, vacuum extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 36 publications
3
41
0
1
Order By: Relevance
“…Hypovolemic shock, disseminated intravascular coagulation, and multiorgan failure can develop in this setting and lead to neonatal death in up to 25% of cases. [11][12][13] The mechanism of injury for a subgaleal hemorrhage is thought to be the vacuum traction pulling the scalp away from a stationary bony calvarium thus avulsing open the subgaleal space causing the bridging vessels to tear and bleed into the subgaleal space. 7 Continued bleeding would occur until tamponade occurs from pressure.…”
Section: Soft Tissue Injury To the Head And Neckmentioning
confidence: 99%
“…Hypovolemic shock, disseminated intravascular coagulation, and multiorgan failure can develop in this setting and lead to neonatal death in up to 25% of cases. [11][12][13] The mechanism of injury for a subgaleal hemorrhage is thought to be the vacuum traction pulling the scalp away from a stationary bony calvarium thus avulsing open the subgaleal space causing the bridging vessels to tear and bleed into the subgaleal space. 7 Continued bleeding would occur until tamponade occurs from pressure.…”
Section: Soft Tissue Injury To the Head And Neckmentioning
confidence: 99%
“…6,7 There are few studies investigating the morbidity related to rotational vacuum extraction or manual rotation. [8][9][10] In these case studies morbidity has been reported in comparison with the morbidity associated with a non-rotational operative vaginal delivery or a spontaneous vaginal birth.…”
Section: Introductionmentioning
confidence: 99%
“…Subgaleal haemorrhage although rare, is associated with significant morbidity and mortality. Uchil et al in 2003 reported incidence of subgaleal haemorrhage in 0.4/1000 cases of spontaneous vaginal births and 5.9/1000 cases of vacuum births [4]. On careful examination of medical records at the time of delivery, we found that proper surveillance methods were adapted from the RANZCOG Recommendations [7] & there was no reported abnormality regarding -heart rate, respiratory rate, colour (pallor) and activity.…”
Section: Discussionmentioning
confidence: 93%
“…Subgaleal haemorrhage is most serious complication of instrumental delivery, although rare, is associated with significant morbidity and mortality [3]. As it is not limited by suture line, the newborn can therefore lose up to 80% of their blood volume within the subaponeurotic space resulting in hypovolemic shock, acute anaemia, coagulopathy and death [4] but volume of subgaleal bleed was much less in this case. Thirdly we focussed on biochemical examination of fluid found at the tracheo-bronchial region.…”
Section: Introductionmentioning
confidence: 87%